Clinical phenotypes and genetic features of epilepsy children with MBD5 gene variants - Jing, X W (Zhonghua er ke za zhi = Chinese journal of pediatrics, 2022)
Objective: To summarize the phenotypes of epilepsy in patients with MBD5 gene variants. Methods: A total of 9 epileptic patients, who were treated in the Department of Pediatrics, Peking University First Hospital from July 2016 to September 2021 and detected with MBD5 gene pathogenic variants, were enrolled. The features of clinical manifestations, electroencephalogram (EEG), and neuroimaging were analyzed retrospectively. Results: Among 9 patients, 6 were male and 3 were female. Age at seizure onset ranged from 5 to 89 months. Multiple seizure types were observed, including generalized tonic clonic seizures (GTCS) in 7 patients, myoclonic seizures in 5 patients, focal seizures in 5 patients, atypical absence seizures in 3 patients, atonic seizures in 2 patients, myoclonus absence seizures in 1 patient, epileptic spasms in 1 patient, and tonic seizures in 1 patient. There were 8 patients with multiple seizure types, 2 patients with sensitivity to fever and 5 patients with clustering of seizures. Two patients had a history of status epilepticus. All patients had developmental delay before seizure onset. Nine patients had obvious language delay, and 6 patients had autism-like manifestations. Five patients had slow background activity in EEG. Interictal EEG showed abnormal discharges in 9 patients. Brain magnetic resonance imaging (MRI) was normal in all patients. A total of 9 epileptic patients carried MBD5 gene variants, all of them were de novo variants. There were MBD5 gene overall heterozygous deletion in 1 patient, large fragment deletions including MBD5 gene in 3 patients and single nucleotide variations (c.300C>A/p.C100X, c.1775delA/p.N592Tfs*29, c.1759C>T/p.Q587X, c.150_151del/p.Lys51Asnfs*6, c.113+1G>C) in 5 patients. The age at last follow-up ranged from 2 years and 9 months to 11 years and 11 months. At the last follow-up, 2 patients were seizure-free for more than 11 months to 4 years 6 months, 7 patients still had seizures. Conclusions: The initial seizure onset in patients with MBD5 gene variants usually occurs in infancy. Most patients have multiple seizure types. The seizures may be fever sensitive and clustered. Developmental delays, language impairments, and autistic behaviors are common. MBD5 gene variants include single nucleotide variations and fragment deletions. Epilepsy associated with MBD5 gene variants is usually refractory